2021
DOI: 10.48550/arxiv.2112.12625
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison and Analysis of Image-to-Image Generative Adversarial Networks: A Survey

Abstract: Generative Adversarial Networks (GANs) have recently introduced effective methods of performing Imageto-Image translations. These models can be applied and generalized to a variety of domains in Image-to-Image translation without changing any parameters. In this paper, we survey and analyze eight Image-to-Image Generative Adversarial Networks: Pix2Px, CycleGAN, CoGAN, StarGAN, MU-NIT, StarGAN2, DA-GAN, and Self Attention GAN. Each of these models presented state-of-the-art results and introduced new techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…89 In the DL literature, many supervised and unsupervised image translation architectures exist, but only a small subset have been applied to medical data. A more complete review of these architectures can be found in Alotaibi et al 90 and Pang et al, 91 with benchmarks of various networks on some of the most common datasets in Saxena et al 92 Interestingly, unpaired training configurations outperformed paired training for cycle-GAN in terms of relative MAE improvements (see Figure 6; 55.98% vs. 47.61%, p = 0.16). However, the results narrowed when studies with similar training set sizes were compared,with paired implementations performing slightly better (53.65% vs. 51.83%, p = 0.29).…”
Section: Recommendations For Researchersmentioning
confidence: 95%
“…89 In the DL literature, many supervised and unsupervised image translation architectures exist, but only a small subset have been applied to medical data. A more complete review of these architectures can be found in Alotaibi et al 90 and Pang et al, 91 with benchmarks of various networks on some of the most common datasets in Saxena et al 92 Interestingly, unpaired training configurations outperformed paired training for cycle-GAN in terms of relative MAE improvements (see Figure 6; 55.98% vs. 47.61%, p = 0.16). However, the results narrowed when studies with similar training set sizes were compared,with paired implementations performing slightly better (53.65% vs. 51.83%, p = 0.29).…”
Section: Recommendations For Researchersmentioning
confidence: 95%
“…The generator takes an input image and generates an output image, while the discriminator differentiates between the real and fake output images. The translation processes from one domain to the other were translated numerically as the generator loss values, which are considered the objective equivalent of determining whether the model was implemented correctly (Saxena, Teli, 2021). To generate new architectural images from a sound file, the pix2pix algorithm was trained with spectrogram files as source files, and architectural images as target files.…”
Section: Pix2pix Based Modelmentioning
confidence: 99%
“…One type of Generative Adversarial Network, a CycleGAN, is designed for image translation [16] and can alleviate this issue. It is trained using an adversarial process involving generators and discriminators, but a CycleGAN has two pairs.…”
Section: Introductionmentioning
confidence: 99%